Association of HSP70 Gene Polymorphism with Heat Stress Indicators in Different Poultry Genetic Groups - Parte, Padma; Sahoo, S. K.; Dubey, P. P.; Kaur, Simarjeet; Mukhopadhyay, C. S. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during January to December, 2023 at Poultry Research Farm overseen by the Directorate of Livestock Farms, GADVASU, Ludhiana, Punjab, India to study and correlate the allelic variations, if any of different HSP70 genotypes with heat stress indicators viz. average daily gain (ADG) and cloacal temperature in three breeds of poultry birds. 300 birds (100 each from three breeds i.e., Kadaknath, RIR and Punjab Brown) were raised under standard feeding and managemental conditions. Body weight was taken at fortnightly intervals from 0day upto 26th week of age. Cloacal temperature was recorded weekly twice during 18th to 26th week. Blood samples were collected from 36 representative birds (12 from each breed) at 25th week of age. The DNA was extracted using phenol chloroform method and PCR standardization was done. Punjab Brown birds had significantly (p≤0.01) higher values for ADG as compared to RIR and Kadaknath at different age groups.785bp HSP70 gene amplicon was sequenced and two genotypes AG and GG were identified with frequencies of 0.6 and 0.4. Distinct alterations in translating amino acid positions, single nucleotide polymorphisms (SNPs), deletions and mutations were observed in all the studied genetic groups, however, the genotypes had no significant effect on average daily gain or cloacal temperature.